Argumentação e a formação do sujeito aluno-autor: processos de (re)significação do dizer na era digital - ANTUNES, Glauce Correa (Universidade Federal do Pará, 2018)
The present work aims to discuss, from the perspectives related to the verbal interaction and discursive genres postulated by Bakhtin (2003), Bakhtin/Volochínov (2006) and Geraldi (1997) and reading and writing conceptions proposed by Kleiman (2013) and Antunes (2005, 2009, 2012), how we can contribute to broadening reading and writing skills, promoting the contextual use of the chosen discourse genre, namely the letter. Our studies were also based on Rojo and Barbosa (2015), Rojo (2013) and Araújo and Leffa (2016) regarding the use of new technologies in school. As for the type of research, in relation to the procedures, it is an action-research and participant; about the approach, is qualitative, with ethnographic traits, since it involves the improvement of teaching practices through our interferences, whose information was gathered through a field work. The subjects selected for the survey are 8th grade students from the municipal public-school system in Belém. The corpus of this research is composed of handwritten letters and Facebook posts produced by the mentioned students. As a general objective, we intend to verify in what sense the writing of the discursive letter genre mobilizes different knowledge when it is used in school practices centered as close as possible to the linguistic situations of the students. Regarding the specific objectives, we intend: (i) to ascertain how these same subjects behave in a context with the singularities of the virtual world; and (ii) to verify how the use of speech sequencers facilitates the construction of meanings in their productions. To do this, we introduce the use of Facebook so that they also position themselves as critical readers, in order to compare what differentiates their critical online position from conventional writing, thus comparing the contexts of production and the differences that this implies in the lexical choices. In addition to the aforementioned authors, we have been in Lopes-Rossi (2008) and Solé (1998), which have led some of the guidelines we have proposed to achieve our objectives. To reach them and consolidate our analyzes, we applied an intervention proposal, carried out in the form of a teaching project, with modules for reading, writing and dissemination, which culminated in exchanges of letters between school students in different cities (Belém and Tomé-Açu) and posts in the profiles of our students from Belém. The results point out that there is a change of posture when the student-author subject is faced with a linguistic situation in which, in fact, there is a real interlocutor and the writing becomes significant and makes different grammatical, lexical and phraseological choices when structuring its statement in front of different interlocutors.